16S rDNA Pyrosequencing Analysis of Bacterial Community in Heavy Metals Polluted Soils - Gołębiewski, Marcin (Springer US, 2014)
Soil contamination with heavy metals is a widespread problem, especially prominent on grounds lying in the vicinity of mines, smelters, and other industrial facilities. Many such areas are located in Southern Poland; they are polluted mainly with Pb, Zn, Cd, or Cu, and locally also with Cr. As for now, little is known about most bacterial species thriving in such soils and even less about a core bacterial community—a set of taxa common to polluted soils. Therefore, we wanted to answer the question if such a set could be found in samples differing physicochemically and phytosociologically. To answer the question, we analyzed bacterial communities in three soil samples contaminated with Pb and Zn and two contaminated with Cr and lower levels of Pb and Zn. The communities were assessed with 16S rRNA gene fragments pyrosequencing. It was found that the samples differed significantly and Zn decreased both diversity and species richness at species and family levels, while plant species richness did not correlate with bacterial diversity. In spite of the differences between the samples, they shared many operational taxonomic units (OTUs) and it was possible to delineate the core microbiome of our sample set. The core set of OTUs comprised members of such taxa as Sphingomonas, Candidatus Solibacter, or Flexibacter showing that particular genera might be shared among sites ~40 km distant. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00248-013-0344-7) contains supplementary material, which is available to authorized users.